Quantitative determination of imatinib stability under various stress conditions - Khalid Mohammed Alkharfy; Rao Muzaffer Ali Khan; Majed Al-Asmari; Baderelddin Hashim Alhadeyah; Ajaz Ahmad (Wolters Kluwer Medknow Publications, 2013)
Objective: A simple, rapid, reverse phase and stability-indicating high-performance liquid chromatography (HPLC) method for the estimation of imatinib in solution and in plasma under forced degradation conditions was developed. Materials and Methods: The method employed isocratic elution using a Waters Atlantis C18 (5 μ, 4.6 mm × 150 mm) HPLC column. The mobile phase consisted of acetonitrile and 10 mM KH 2 PO 4 buffer in the ratio of 35:65 (v/v, pH = 4.6), which was delivered using isocratic flow at a rate of 1 mL/min. The injection volume of 50 μL and imatinib was monitored using UV detection 270 nm after a clean-up step with diethyl ether and with a total run time of 6 min. Results: The method was validated in solution as well as in plasma, and the response was found to be linear in the concentration range of 0.5-20 μg/mL. The coefficient of correlation was found to be >0.99. Forced degradation studies revealed that imatinib undergoes degradation under different stress conditions. Discussion: The developed HPLC method could effectively resolve degradation product peaks from imatinib except at neutral pH. Further, no interference was found at the retention time of imatinib from any plasma components, indicating selectivity of the developed method. The limits of detection and quantitation of the method were 0.025 and 0.5 μg/mL, respectively.